Mechanisms and genetic mutations of pyrethroid resistance in Aedes albopictus in the context of urbanization: a case study of Hangzhou, China - Jin, Binbin; Wei, Lingya; Duan, Tianxiao; Wang, Yinghong; Wang, Huimin; Jin, Hui (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe Asian tiger mosquito (Aedes albopictus) serves as a globally significant vector for arboviruses such as dengue, chikungunya, and Zika. The extensive application of pyrethroid insecticides has led to a growing resistance in Ae. albopictus populations, thereby compromising mosquito control initiatives. This study examines the mechanisms underlying pyrethroid resistance and the related genetic mutations in Ae. albopictus within the framework of urbanization, with the objective of informing the development of effective control strategies.MethodsAe. albopictus larvae were sampled from five districts in Hangzhou, China, each characterized by different levels of urbanization. Resistance to beta-cypermethrin and permethrin were evaluated utilizing the World Health Organization (WHO) tube test methodology. Molecular analyses were conducted to identify mutations in the voltage-gated sodium channel (VGSC) gene, with a specific focus on the F1534S mutation. The data were subjected to statistical analysis using Fisher’s exact test, chi-square test, and Pearson correlation to assess the relationship between resistance levels and urbanization.ResultsPopulations of Ae. albopictus in Hangzhou demonstrated substantial resistance to pyrethroids, with mortality rates falling below 90%. Notably, the Binjiang District exhibited the lowest mortality rates, with 20.55% for beta-cypermethrin and 21.21% for permethrin, whereas Chun’an County displayed relatively higher mortality rates of 32.00% and 47.28%, respectively. The F1534S mutation was predominantly observed, with homozygous (S/S) mutations constituting 87.78% and 83.29% of the populations exposed to beta-cypermethrin and permethrin, respectively. Chi-square analyses confirmed a significant association between the F1534S mutation and resistance (P < 0.01). Furthermore, no significant correlation was identified between resistance levels and urbanization rates (P > 0.05), indicating that urbanization is not a primary factor contributing to resistance.ConclusionThe F1534S mutation is pivotal in conferring pyrethroid resistance in Ae. albopictus. To enhance the effectiveness of mosquito control strategies, it is imperative to incorporate resistance monitoring, insecticide rotation, and non-chemical approaches. Additionally, further research is warranted to investigate alternative resistance mechanisms and the influence of urbanization on mosquito ecology.